Solid air : Australian and New Zealand spoken word - Stavanger, David; Te Whiu, Anne-Marie (University of Queensland Press, 2019)
A ground-breaking and original collection that celebrates Australia and New Zealand's leading performance poets, direct from stage to page. Over the past decade, Spoken Word has established itself as a central part of contemporary Australian and New Zealand poetry. For the first-time ever, these voices are transported from the stage to the page, captured in print so that the spoken-word experience can be shared with a new and broader audience. Solid Air showcases the work of more than 100 performance poets - combining elements of slam, hip-hop and experimental performance poetry - to deliver an unforgettable reading experience that is both literary and loud. Poems capture themes of modern culture, identity and resistance. Contributors include: Ali Cobby Eckermann, Hera Lindsay Bird, Claire G. Coleman, Omar Musa, Maxine Beneba Clarke, Behrouz Boochani, Taika Waititi, Courtney Barnett, Michelle Law, Hannah Gadsby, Luka Lesson and many, many more.